2020
DOI: 10.1155/2020/6620539
|View full text |Cite
|
Sign up to set email alerts
|

Risk Identification and Responses of Tunnel Construction Management during the COVID‐19 Pandemic

Abstract: The COVID-19 pandemic has brought about significant influences to the world, including tunnel construction. Based on the analysis of 12 tunnel construction projects, this paper identifies the specific risk factors related to the COVID-19 pandemic, e.g., men, materials, machines, methods, social environment, and political epidemic prevention pressure. Among these risk factors, worker availability, site accessibility, shortage of construction materials, and inadequate epidemic prevention materials caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…However, H&S budget cuts adversely affect H&S functions such as training (Boustras and Guldenmund, 2018), the purchase of PPE (Cohen and Rodgers, 2020;Watterson, 2020) and enforcement of H&S provisions (Watterson, 2020). The disruption of global supply chains affected the supply of PPE and other essentials for H&S and exerted an upward pressure on the price of PPE (Cohen and Rodgers, 2020;Comptroller and Auditor General, 2020;Wang et al, 2020). This observation corroborates Occupational Safety and Health Administration (OSHA) (2009), which highlighted that logistical and economic considerations affected the provision of PPE during the 2009 H1N1 influenza pandemic.…”
Section: The Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, H&S budget cuts adversely affect H&S functions such as training (Boustras and Guldenmund, 2018), the purchase of PPE (Cohen and Rodgers, 2020;Watterson, 2020) and enforcement of H&S provisions (Watterson, 2020). The disruption of global supply chains affected the supply of PPE and other essentials for H&S and exerted an upward pressure on the price of PPE (Cohen and Rodgers, 2020;Comptroller and Auditor General, 2020;Wang et al, 2020). This observation corroborates Occupational Safety and Health Administration (OSHA) (2009), which highlighted that logistical and economic considerations affected the provision of PPE during the 2009 H1N1 influenza pandemic.…”
Section: The Review Of Related Literaturementioning
confidence: 99%
“…This observation corroborates Occupational Safety and Health Administration (OSHA) (2009), which highlighted that logistical and economic considerations affected the provision of PPE during the 2009 H1N1 influenza pandemic. Taking into consideration the preceding discussion, the additional H&S procedures to reduce the risk of occupational infection with SARS-CoV-2 will increase the cost of implementing H&S provisions (Jones et al, 2020;Wang et al, 2020).…”
Section: The Review Of Related Literaturementioning
confidence: 99%
“…COVID-19 was declared as a Public Health Emergency of International Concern on 30 January 2020 by the World Health Organization (WHO) and subsequently as a pandemic by the same organisation on 11 March 2020 (VERTIC, 2020). This global pandemic had an immediate catastrophic effect on human lives and many countries' economy (Harinarain, 2020;Wang et al, 2020). In an attempt to mitigate the spread and disastrous effect of the virus, WHO, the Centres for Disease Control and Prevention (CDC) and several governments developed protocols and guidelines to guide the operations of all organisations, including construction firms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done in the area of construction health and safety globally (Smallwood and Haupt, 2006;Construction Industry Development Board (CIDB), 2009;Andolfo and Sadeghpour, 2015;Chandi et al, 2018;Dutta et al, 2020). Moreover, studies on the effect of COVID-19 on the construction industry have been conducted in several countries (Avice, 2020;Bsisu, 2020;Gamil and Alhagar, 2020;Harinarain, 2020;Jallow et al, 2020;Wang et al, 2020;Agyekum et al, 2021;Stiles et al, 2021;Simpeh and Amoah, 2021). For example, the result of a study conducted in USA reveals that the nature of construction makes it difficult to implement the new COVID-19 safety regulations on sites (Avice, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the World Health Organisation (WHO) and the Centres for Disease Control and Prevention (CDC) have provided guidelines and measures to govern how organisations operate. Although several studies on the effect of COVID-19 on the construction industry have be done across the world (Avice, 2020;Bailey et al, 2020;Bsisu, 2020;Gamil and Alhagar, 2020;Harinarain, 2020;Jallow et al, 2020;Ogunnusi et al, 2020;Wang et al, 2020;Stiles et al, 2021), there is no evidence of how South African construction companies have incorporated COVID-19 measures into the site health and safety policies and how such policies are enforced. Yet, Małecka et al (2020) revealed that authorities' recommendations are not fully implemented.…”
Section: Introductionmentioning
confidence: 99%